Characteristic of Secondary Intraocular Lens Implantation in Aphakic Children in Cicendo National Eye Hospital - Lina Sudaryo (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2022)
Background: Pediatric cataract is responsible for 200.000 of preventable blindness in children. Early cataract extraction and correction after the lens removal is critical. Secondary intraocular (IOL) implantation might be considered when the child is intolerant to contact lenses/spectacle wear. Only a few study has been done regarding secondary IOL implantation in aphakic children. Objective: This study was aimed to describe the characteristic of secondary IOL implantation in aphakic children in Cicendo National Eye Hospital. Methods: This retrospective observational study took samples from medical records of patients who underwent secondary IOL implantation in 2016 – 2020 in Cicendo National Eye Hospital. Results: Fifty nine eyes of forty pediatric patients underwent secondary IOL implantation surgery between 2016 – 2020. Two patients were excluded. From the 38 patients, 56 eyes were observed. Total of 20 patients were boys (52.6%) and 71.1% cases were bilateral cataract with congenital cataract as the main initial diagnosis (47.4%). Mean age of secondary IOL implantation was 71 ± 35 (20–201) months. Mean duration between cataract surgery and secondary IOL implantation was 51 ± 36 (2 – 189) months . Total of 80.4% of the IOL were fixated in the sulcus. Only 25% remained present for more than 12 months follow up and 65.8% of patients were corrected with bifocal spectacles. Conclusion: Secondary IOL implantation in aphakic children were mostly done in the age of six years old. Most of the IOL were fixated in the sulcus. Patients were mostly given bifocal spectacles.